The virtual campus and gamification of the teaching/learning process: A special reference to the legal subjects that are articulated outside the Bachelor’s Degree in Law - Serrano García, Mª José (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This article presents the result of the implementation of a novel teaching methodology that seeks to overcome the difficulties that the teaching/learning process encounters in legal subjects that form part of non-legal university degrees. It begins by highlighting the role of information and communication technologies in this process and, significantly, the virtual campus. Then, it describes each of the elements of the teaching methodology applied, including gamification. Finally it concludes with the determination of the consequences of the experience developed.